PWE-199 Metabolomic profiling in acute pancreatitis; in search of new biomarkers. (22nd June 2015) - Ross, NP; Correa, ES; Rattray, NJ; Hildebrand, DR; Trivedi, DK; Goodacre, R; Watson, AJ
Abstract : Introduction: Severe acute pancreatitis (AP) carries a 30–50% mortality. 1 Current scoring systems fall short in predictive accuracy, sensitivity, specificity and availability. 2 Metabolomics aims to decipher molecular signatures that will distinguish disease from controls, ultimately leading to novel targets for diagnosis, staging and treatment. Initial studies are discovery-based, hypothesis-generating and typically aim to establish a snapshot of the metabolism of an individual by metabolite profile. The aim of this study was to determine the urinary and serum metabolomic profiles of AP in comparison to healthy controls and establish if metabolomic profiling can distinguish severity or aetiology of disease in order to identify potential novel bio-markers. Method: Urine and serum samples from 72 patients with AP, were compared with 62 healthy controls (HC). Two analytical platforms, UHPLC-MS and GC-TOF-MS, were used in this study in order to minimise false negatives and identify a quantitative compliment of all metabolites across a wide molecular weight range. GC-TOF-MS can identify VLMW polar metabolites (<350 Da), where-as reverse phase UHPLC-MS is useful in detecting non-polar metabolites. Metabolite identification was subject to univariate and multivariate analysis (p < 0.05). Results: After univariate analysis, a total of 964 serum metabolites and 1263 urinary metabolites were identified as significantly different in comparison to HC. Multivariate analysis showed good discrimination, based on metabolite profiles, between severity of AP when classified by MODS but not by APACHE II score. There was no separation by metabolite profiles correlating to aetiology of AP. Conclusion: In this novel study, metabolite profiling can distinguish patients with AP from controls and appears to differentiate severity by MODS criteria. Fatty acids, glycerophoshocholines, eicosanoids, TCA cycle intermediates and melatonin levels were altered in AP in comparison to controls. These metabolites offer insights into pathogenesis and may represent future putative biomarkers. Disclosure of interest: None Declared. References: Mofidi R, et al . 2006. Association between early systemic inflammatory response, severity of multiorgan dysfunction and death in acute pancreatitis. Br. J. Surg. 93(6), pp. 738-744. Papachristou GI, et al . Predictors of severity and necrosis in acute pancreatitis. Gastroenterology clinics of North America, 33(4):871–890.